A triple‐blind, placebo‐controlled, randomized clinical trial to evaluate the effect of curcumin‐containing nanomicelles on cellular immune responses subtypes and clinical outcome in COVID‐19 patients. (19th September 2021) - Hassaniazad, Mehdi; Eftekhar, Ebrahim; Inchehsablagh, Behnaz Rahnama; Kamali, Hossein; Tousi, Abdolali; Jaafari, Mahmoud Reza; Rafat, Milad; Fathalipour, Mohammad; Nikoofal‐Sahlabadi, Sara; Gouklani, Hamed; Alizade, Hesam; Nikpoor, Amin Reza
Abstract : In COVID‐19 patients, cytokine storm due to excessive immune responses can cause severe complications. In this study, we investigated the effect of curcumin nanomicelles on clinical outcome and cellular immune responses subtypes changes in COVID‐19 patients. A randomized, triple‐blinded, placebo‐controlled study was done. Forty COVID‐19 patients were included into two groups of nano‐curcumin and placebo. The nano‐curcumin group received 40 mg of nano‐curcumin capsule, four times per day for 2 weeks. Clinical signs and gene expression of TBX21, GATA3, RORC and FOXP3 genes and IFN‐γ, IL‐4, IL‐17 and TGF‐β cytokines serum levels were measured at time points of 0, 7 and 14 days. Serum levels of IFN‐γ ( p  = .52) and IL‐17 ( p  = .11) decreased, while IL‐4 ( p  = .12) and TGF‐β ( p  = .14) increased in the nano‐curcumin group compared with placebo on day 14. Moreover, gene expressions of TBX21 ( p  = .02) and FOXP3 ( p  = .005) genes were significantly decreased and increased between nano‐curcumin and placebo groups on day 7, respectively. It can be concluded that administration of nano‐curcumin in inflammatory phase of COVID‐19 can accelerate recovering of the acute inflammatory phase by modulating inflammatory immune responses. Therefore, it is suggested that this supplement in inflammatory diseases, including COVID‐19, can be effective in controlling the inflammatory responses.